"I have never known such undisguised arson": The Ladysmith Rag, the Mafeking Bonfire and the Battle for Order in Late Nineteenth-Century Cambridge. (May 2014) - Lang, Seán
Abstract : The celebrations in Cambridge to welcome the relief of Ladysmith in March 1900 took the form of a huge illegal bonfire erected in the town market place by students and townspeople, fed by wood taken without permission from public and private buildings in the city and accompanied by a firework fight. This was the third such bonfire to be lit in the market place in almost as many years, the first two prompted by the university's rejection of degrees for women in 1897 and by a visit to Cambridge by Lord Kitchener in 1898, and it therefore contributed to a rapidly-developing crisis over the extent and effectiveness of the control exercised at street level by both the city and the university authorities. The controversy sparked off by the relief of Ladysmith gave particular importance to the preparations being made for the expected relief of Mafeking later in the year, which became the vehicle for an effective reassertion of authority and control by the city council. The article also considers the way in which the bonfires reflected conflicting perceptions of masculinity and the long-running rivalry between the university and the town.